China's education sector: Investigating factors to improve business operational efficiency in a highly competitive environment - Yu, Jing; Wider, Walton; Lajuma, Surianti; Khadri, Mohd Wafiy Akmal B Ahmad; Chan, Choon Kit; Maidin, Siti Sarah (International Journal of Management and Sustainability, 2024)
The purpose of this study is to investigate the human factor, organisational factor, and political factor for enhancing business operational efficiency in a highly competitive environment in China's education sector. On a global scale, China has garnered recognition for its achievements in the field of education. However, there are significant differences in higher education resource allocation among the many Chinese provinces as a result of the pursuit of scale and speed, as well as unequal development across the country. Therefore, there is a need to investigate the factors that influence the operational efficiency of the Chinese educational sector in a highly competitive environment. A cross-sectional design was utilised to conduct an online survey with 121 education sector employees. According to the findings, the organisational factor is the strongest predictor of business operational efficiency, followed by the political factor. The human factor, however, was not a significant predictor. This study discovered that changes in organisational and political factors can have an impact on the operational efficiency of any educational sector. As a result, it is suggested that clear reporting and an organised hierarchical structure be implemented across all departments. As a result, the educational institute will be able to maintain its business operational efficiency more easily.